Performance assessment in the commercial off-the-shelf receiver radio occultation mission on VELOX-CI satellite - Li, Bing-Xuan (2022)
VELOX-CI was launched on December 16, 2015 into the near-equatorial orbit. It is the second micro-satellite of Satellite Research Center (SaRC) in Nanyang Technological University in Singapore. VELOX-CI is designed to explore the potential of using the commercial-off-the-shelf (COTS) GPS receivers for RO mission for the first time. Three GPS antennas are located at the zenith, forward-velocity, and after-velocity directions. In total, VELOX-CI collected 240 radio occultation (RO) missions (570 h) from 2015 to 2018 with mission durations ranging from 0.5 to 16.7 h. The lowest penetration altitude from the COTS receivers reaches 6 km. In this paper, the RO performance of the VELOX-CI is evaluated and validated with both ground-based and space-based measurements. Tropospheric and ionospheric profiles obtained from VELOX-CI are also compared with assimilative atmospheric models and empirical ionospheric models, respectively. Results show that with proper sampling frequencies (5–20 Hz), the refractivity error estimated by VELOX-CI RO is below 5% at altitudes below 25 km compared to reanalysis model estimations and radiosonde measurements. The observed ionospheric peak density and height show reasonable ranges for both daytime and nighttime. This study demonstrates the capability of COTS receiver in observing atmospheric and ionospheric parameters. In the future, utilizing COTS receivers with lower-cost low Earth orbit (LEO) satellite missions can largely increase the data volume of RO and enhance our capability in monitoring the Earth's atmosphere.